Pentingnya Pencatatan Keuangan Dan Pencantuman Label Halal Produk Pada Home Industry Abon Ikan Tuna Segar G&R Masohi Shop Di Kelurahan Lesane Kecamatan Kota Masohi Kabupaten Maluku Tengah - Dwi Hariyanti; Wa Asrida; Sri Astuti Musaid; Tri Retno Hariyati (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
This community service was performed at the home industry of G&R Masohi Shope in Lesane Village, Masohi City District, Central Maluku Regency. This devotional activity is carried out with the aim to: 1) provide understanding and assistance to partners "G&R Masohi Shop" regarding the correct recording of business finance in accordance with accounting rules to know the development of partner business, 2) Provide understanding and assistance to partners "G&R Masohi Shope" ways and procedures of managing halal certificate of products from LP-POM MUI Maluku Province, in order to obtain permission to list halal labels on product packaging. The method of implementing community service activities used by the service team to solve partner problems is the method of training and mentoring. The result of this devotional activity is 1) The Partner is able to do the financial recording of his business well so as to maintain the existence and sustainability of his business, 2) The partner obtains halal certificate of fresh tuna fish abon products from LPPOM MUI Maluku Province which can be included in the packaging of fresh tuna fish abon products G&R Masohi Shop.